2008
DOI: 10.1530/eje-07-0649
|View full text |Cite
|
Sign up to set email alerts
|

Association of an A/C single nucleotide polymorphism in programmed cell death-ligand 1 gene with Graves' disease in Japanese patients.

Abstract: Objective: Programmed cell death-1 (PD-1) and its ligands (PD-L1 and PD-L2) inhibit T-cell proliferation and activation. This inhibition down-regulates the immune responses. The association of a PD-L1 polymorphism with Graves' disease (GD) was studied. Design: The association of an A/C polymorphism at position 8923 in PD-L1 intron 4 with GD was studied. Patients: The study included 327 GD patients and 192 controls, of which 252 GD patients were followed over 5-10 years. Measurements: PD-L1 intron 4 position 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 45 publications
0
33
1
Order By: Relevance
“…In this study, however, we did not find any association of PD-1 rs2227981 and rs10204525, PD-L1 rs197000 and PD-L2 rs7854303 SNPs with Behcet's disease. These results are in disagreement to those seen in other autoimmune diseases reported among different ethnic groups [16][27], [33], [34]. This may be explained by the fact that the etiology and pathogenesis of Behcet's disease may be different from other autoimmune diseases [3].…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…In this study, however, we did not find any association of PD-1 rs2227981 and rs10204525, PD-L1 rs197000 and PD-L2 rs7854303 SNPs with Behcet's disease. These results are in disagreement to those seen in other autoimmune diseases reported among different ethnic groups [16][27], [33], [34]. This may be explained by the fact that the etiology and pathogenesis of Behcet's disease may be different from other autoimmune diseases [3].…”
Section: Discussioncontrasting
confidence: 74%
“…Our previous study has demonstrated that PD-1 rs2227981 may be negatively associated with the extraocular manifestations of Vogt-Koyanagi-Harada syndrome in a Chinese Han population [32]. Although the PD-L1 rs1970000 polymorphism locates in intron 4, which does not affect an amino acid substitution, it may be close to or within transcriptional factor-binding sites [23] and may thus influence the expression of the PD-L1 gene through modifying the binding affinity of transcriptional factors [34]. This polymorphism has been shown to be associated with GD in Japanese patients [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After baseline fluorescence measurements at 25 °C, the PCR protocol included a 10-min incubation at 95 °C, 40 cycles of denaturing at 92 °C for 15 s and annealing and extending at 60 °C for 1 min, and a final measurement of fluorescence at 60 °C. SNPs with previously described associations or putative functional effects were selected24252627283940414243.…”
Section: Methodsmentioning
confidence: 99%